Research Into the Effect of Proton Pump Inhibitors on Lungs and Leukocytes - Ozatık, Orhan; Ozatık, Fikriye Yasemin; Teksen, Yasemin; Dag, Ilknur; Saygılı, Suna; Koçak, Ahmet (Turkish Journal of Gastroenterology, 2021)
Background: Proton pump inhibitors (PPI) are the most commonly used medication in the world. They are prescribed as an effective treatment choice for gastrointestinal system diseases linked to hyperacidity, especially. Additionally, non-indication and unnecessary use are very common. Many publications in recent times have reported significant side effects. However, there are insufficient studies about the mechanism for these side effects. Methods: Twenty-four Wistar albino rats were used in this study. Rats were divided into 3 groups of control, group-administered H2 receptor blockers and a group-administered PPI. Medications were administered for 30 days intraperitoneal. After 30 days, rats were euthanized and lung tissue was obtained. Lung was stained for immunohistochemical catalase, superoxide dismutase, Glutathione peroxidase, myeloperoxidase, and toluidine blue and investigated with a light microscope. Transmission electron microscopy (TEM) was used to investigate lung tissues and neutrophil leukocytes. Additionally, lung tissue had biochemical hydrogen peroxide (H2O2) levels researched. Results: H2O2 amounts, produced by lysosomes with important duties for neutrophil functions in lung tissues, were found to be statistically significantly reduced in the group-administered PPI. Results from investigations of specimens obtained with immunohistochemical staining observed increases in antioxidant amounts in the PPI group. Investigation with TEM identified more inflammation findings in the lung tissue from the group-administered PPI compared to the control group and the group-administered H2 receptors. Conclusion: In conclusion, we identified long-term PPI use disrupts neutrophil leukocyte functions in the lung. All clinicians should be much more careful about PPI use.